(untitled) (Journal of Research Updates in Polymer Science, 2015)
Cenosphere fly ash is a byproduct of coal combustion processes of power plants. It is composed of hollow, hard shelled, minute spheres, which are made up of silica, iron, and alumina. In this study, cenosphere fly ash is incorporated into rigid PVC foam to improve thermal and mechanical properties of their composites. Microstructural, physical, mechanical, and thermal properties of rigid PVC foam extruded with different loadings of cenosphere fly ash (6, 12, 18phr) are characterized. The measured density of the extruded PVC foam composites increased with cenosphere content, indicating a hindrance to the foaming process. Tensile and flexural mechanical properties improved at higher cenosphere content, while the impact strength decreased at initial loading of 6 phr of cenosphere particles and remained steady at higher loadings. Thermal characterization of the extruded samples showed that glass transition temperature remained almost unaffected, while TGA analysis revealed no change in the initial degradation temperature and significant improvement in the final degradation temperature. Thermo-mechanical properties measured by DMA revealed a remarkable improvement in the viscoelastic properties of the composites reinforced with cenosphere particles. SEM analysis of the composites microstructure confirmed that the cenosphere particles were mechanically interlocked with good interfacial interaction in the PVC matrix.